Growth and External Debt Management
XV, 279 p.
Keywords: This volume contains a series of 21 papers presented at the International Conference of Economists, held at the University of Zagreb, Yugoslavia. The contributors discuss policy issues of macro-economic managment and offer general and overall approaches to the debt and growth problems of the 1980s.